Athletic taping, bracing, and casting - Perrin, David H. 1954- PhD, FNATA; McLeod, Ian A. 1975- PA-C, ATC (Human Kinetics, 2019)
The premier text for athletic taping and bracing is back in a stunning fourth edition-an edition expanded to cover casting and splinting techniques. It continues to rise above the rest with superior photos and illustrations, precise step-by-step instructions, and pinpoint focus on the techniques that athletic trainers and therapists are most likely to apply in clinical practice. Author Ian McLeod joins David Perrin in this fourth edition to lend further expertise in the application guidelines and precautions for casting and splinting. Additional enhancements include the following: a new web resource featuring 56 testing checklists that detail the steps required to show competency; online video with demonstrations of proper technique, including six clips dedicated to casting; twenty new casting and splinting techniques for Achilles tendon ruptures and common fractures of the foot, ankle, elbow, wrist, and hand; information about the importance of evidence-based practice for the techniques. Athletic Taping, Bracing, and Casting examines each major joint and body region, covering traditional taping as well as rigid strap taping, elastic kinesiology taping, and techniques for immobilization with casting and splinting. Anatomical descriptions highlight the mechanisms of injury that must be understood to effectively apply taping, bracing, and casting protocols, and basic stretching and strengthening exercises supplement the techniques to further prevent injury and strengthen rehabilitated patients